Consulting report – Agencia B12 - Alfaro Carbajal, Cesar Alberto (2019)
Agencia B12 is a Spanish company with operations in Mexico, Peru and Spain. Agencia B12 develops its operations mainly in digital marketing and call service center. This type of services offered by the firm are operated in the telecommunications companies (such as Movistar, Claro, Bitel and Entel Peru), Agencia B12 works with the main companies in the telecommunication sector, however, Agencia B12 are currently working with some companies which are from other induastrias such as Direct tv and Banco Pichincha. The current purpose of Agencia B12 is to diversify its portfolio of services in order to acquire new sources of revenues. The new projects that Agencia B12 wishes to develop are due to its client portfolio being strongly linked to the telecommunications industry, in response to this situation Agencia B12 wishes to launch Digital collection in order to expand its customer portfolio, venturing into the collection market, working with new clients, in this case the financial entities. Although, the project will initially be launched as a prototype in Peru, the desire of Agencia B12 is to expand this service to other branches.